High-mobility field-effect transistors based on transition metal dichalcogenides - Podzorov, V.; Gershenson, M. E.; Kloc, Christian; Zeis, Roswitha; Bucher, E. (Applied Physics Letters, 2004)
Field-effect transistors (FET) based on transition metal dichalcogenides (TMD) were fabricated. The fabrication of the FET with intrinsically low field-effect threshold and high charge carrier mobility was possible due to the unique structure of single crystals of these layered inorganic semiconductors. Ambipolar operation is demonstrated by the FETs. The combination of the electrical properties and mechanical flexibility make the TBD based field-effect transistors an attractive option for flexible electronics.
Created from Fastlane, Scopus look-up